Factor the expression by grouping. First, the expression needs to be rewritten as -4x^2+ax+bx-6. To find a and b, set up a system to be solved.

You are watching: What is the expression in factored form 4x2+11x+6

Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 24. 4x2+11x-69=0 Two solutions were found : x = -23/4 = -5.750 x = 3 Step by step solution : Step 1 :Equation at the end of step 1 : (22x2 + 11x) - 69 = 0 Step 2 :Trying to factor by ...
Guilherme N. May 25, 2015 You can find its roots and then turn them into factors.Let's use Bhaskara to find them. displaystylefrac-11pmsqrt121-4left(2 ight)left(-6 ight)4 ...
4x2+11x-3 Final result : (4x - 1) • (x + 3) Step by step solution : Step 1 :Equation at the end of step 1 : (22x2 + 11x) - 3 Step 2 :Trying to factor by splitting the middle term ...
4x2+11x-3=0 Two solutions were found : x = -3 x = 1/4 = 0.250 Step by step solution : Step 1 :Equation at the end of step 1 : (22x2 + 11x) - 3 = 0 Step 2 :Trying to factor by splitting ...
6x2+11x-32 Final result : 6x2 + 11x - 32 Step by step solution : Step 1 :Equation at the end of step 1 : ((2•3x2) + 11x) - 32 Step 2 :Trying to factor by splitting the middle term ...
displaystylefleft(x ight)=4left(x^2+3x-16 ight) Explanation: displaystylefleft(x ight)=4y=4left(x^2+3x-16 ight) Factor y. displaystyleD=b^2-4ac=9+64=73 ...
More Items     Factor the expression by grouping. First, the expression needs to be rewritten as -4x^2+ax+bx-6. To find a and b, set up a system to be solved.
Since ab is positive, a and b have the same sign. Since a+b is positive, a and b are both positive. List all such integer pairs that give product 24.
Quadratic polynomial can be factored using the transformation ax^2+bx+c=aleft(x-x_1 ight)left(x-x_2 ight), where x_1 and x_2 are the solutions of the quadratic equation ax^2+bx+c=0.
All equations of the form ax^2+bx+c=0 can be solved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
Factor the original expression using ax^2+bx+c=aleft(x-x_1 ight)left(x-x_2 ight). Substitute frac34 for x_1 and 2 for x_2.

See more: What Does Ljs Mean In Text Ing? What Does Ljs Mean When Texting

Subtract frac34 from x by finding a common denominator and subtracting the numerators. Then reduce the fraction to lowest terms if possible.
left< eginarray l l 2 & 3 \ 5 & 4 endarray ight> left< eginarray l l l 2 & 0 & 3 \ -1 & 1 & 5 endarray ight>    EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు